Предмет: Алгебра,
автор: marena98
Упростить выражения:
1.
2.
Ответы
Автор ответа:
1
1)1/(1+ctgx) -1/(1-ctgx)=(1-ctgx-1-ctgx)/(1-ctg²x)=-2ctgx/(1-ctg²x)=
=-2cosx/sinx :(sin²x-cos²x)/sin²x=2cosx/sinx*sin²x/(cos²x-sin²x)=sin2x/cos2x=tg2x
2)1/(1-tgx)-1/(1+tgx)=(1+tgx-1+tgx)/(1-tg²x)=2tgx/(1-tg²x)=tg2x
=-2cosx/sinx :(sin²x-cos²x)/sin²x=2cosx/sinx*sin²x/(cos²x-sin²x)=sin2x/cos2x=tg2x
2)1/(1-tgx)-1/(1+tgx)=(1+tgx-1+tgx)/(1-tg²x)=2tgx/(1-tg²x)=tg2x
Похожие вопросы
Предмет: Русский язык,
автор: tehnik1710
Предмет: Русский язык,
автор: BlackMangle
Предмет: Английский язык,
автор: Аноним
Предмет: Алгебра,
автор: megamozg62